137 PRIMARY RESULTS FROM APOLLO-B, A PHASE 3 STUDY OF PATISIRAN IN PATIENTS WITH TRANSTHYRETIN-MEDIATED AMYLOIDOSIS WITH CARDIOMYOPATHY. (15th December 2022) - Longhi(on Behalf Of), Simone; Maurer, Mathew S; Fontana, Marianna; Berk, John L; Gustafsson, Finn; Simões, Marcos; Grogan, Martha; Fernandes, Fábio; Gottlieb, Robert L; Kubanek, Milos; Poulsen, Steen; Damy, Thibaud; et al.
Abstract: Background: Transthyretin-mediated (ATTR) amyloidosis is a rapidly progressive, debilitating, and fatal disease caused by misfolded TTR accumulating in multiple organs and tissues. Patients with hereditary (hATTR) amyloidosis (also known as ATTRv amyloidosis) or wild-type (wtATTR) amyloidosis with cardiomyopathy exhibit decreased survival. Patisiran, an IV RNAi therapeutic that inhibits synthesis of wt and variant TTR, was approved for the treatment of hATTR amyloidosis with polyneuropathy. Exploratory analyses of a predefined cardiac subpopulation in the APOLLO study demonstrated the potential for patisiran to improve the manifestations of cardiomyopathy in patients with hATTR amyloidosis with polyneuropathy. Objective: To investigate the safety and efficacy of patisiran in patients with ATTR amyloidosis with cardiomyopathy in the ongoing APOLLO-B study (NCT03997383). Material & Methods: Patients were 18–85 years of age with evidence of cardiac amyloidosis by echocardiography (end-diastolic interventricular wall thickness >12 mm), and either ATTR amyloid deposition on tissue biopsy or fulfilling nonbiopsy diagnostic criteria for ATTR amyloidosis with cardiomyopathy. Patients had a medical history of heart failure (HF) due to ATTR amyloidosis with at least 1 prior hospitalization for HF, or current clinical evidence of HF. Patients were randomized (1:1) to receive patisiran IV 0.3 mg/kg or placebo Q3W for 12 months. After the double-blind, placebo-controlled period, all patients may receive patisiran in an open-label extension period for up to 36 months. The primary endpoint was change from baseline in 6-MWT at Month 12 with patisiran treatment, compared with placebo. Secondary endpoints evaluated the effect of patisiran vs placebo at Month 12 on QOL (KCCQ-OS score) as well as two sets of composite endpoints: 1) All-cause mortality, frequency of CV events (CV hospitalizations and urgent HF visits) and change from baseline in 6-MWT; and 2) All-cause mortality and frequency of all-cause hospitalizations and urgent HF visits. The pharmacodynamic effect of patisiran on serum TTR level (change from baseline through Month 12) was also assessed. Results & Discussion: Enrollment completed (359 patients) in May 2021. About 80% of patients have wtATTR amyloidosis. Primary and secondary endpoint data will be presented, including change in 6-MWT and KCCQ-OS score at Month 12, in addition to safety data. Summary & Conclusion: The primary results of the APOLLO-B study will inform the potential of patisiran as a treatment for the cardiomyopathy of ATTR amyloidosis. APOLLO-B will continue to investigate the efficacy and safety of patisiran on ATTR amyloidosis in an open-label extension period.